Association of Dietary Protein Intake and Grip Strength Among Adults Aged 19+ Years: NHANES 2011–2014 Analysis - Pikosky, Matthew A.; Cifelli, Christopher J.; Agarwal, Sanjiv; Fulgoni, Victor L. (Frontiers in Nutrition, 2022)
Background: Research on the role of protein in the diet has evolved beyond a focus on quantity, to include the impact of its quality and distribution across meal times in an effort to optimize dietary protein recommendations. Objective: To determine the association of dietary protein amount, type and intake pattern with grip strength in adults. Design: Data from the National Health and Nutrition Examination Survey (NHANES) 2011-2014 for adults 19+ years (N=9214) were used with exclusions for pregnant and lactating females. Intakes of dietary total protein (TP), animal protein, (AP, including dairy), plant protein (PP) and leucine (Leu) were determined using day one 24 h dietary recall data after adjusting for the complex sample design of NHANES. Regression analyses were used to assess the association of dietary protein and leucine intake quartiles, and whether consuming >20 g of dietary protein at one or more meals was related to grip strength with adjustment for age, gender, and ethnicity. Results: Mean intakes of TP among adults age 19+ years was 83.6±0.5 g/d and 2/3rd of this was from animal sources (including dairy). Grip strength increased (P<0.05) with increasing quartiles of TP, AP, PP and leucine among all adults 19+ years (β=1.34±0.19, 1.27±0.19, 0.76±0.20, and 1.33±0.23 respectively), 19-50 years (β=1.14±0.27, 1.06±0.25, 0.77±0.30, and 1.18±0.27 respectively), and 51+ years (β=0.95±0.26, 1.08±0.27, and 1.05±0.27 respectively for TP, AP and leucine); however, the increase was more pronounced for AP than PP. Grip strength also increased (P<0.05) with increasing number of meal occasions containing >20 g of dietary protein (β=1.50±0.20, 1.41±0.25, and 0.91±0.37 for 19+, 19-50 and 51+ years respectively) and significant increases were detected for two meals compared to zero meals. Conclusions: Dietary protein quantity, quality and distribution should be considered collectively when looking to optimize protein intake to support muscle strength and function.